Accounting for observation uncertainty and bias due to unresolved scales with the Schmidt-Kalman filter. Issue 1 (1st January 2020) - Bell, Zackary; Dance, Sarah L.; Waller, Joanne A.
Abstract: Data assimilation combines observations with numerical model data, to provide a best estimate of a real system. Errors due to unresolved scales arise when there is a spatio-temporal scale mismatch between the processes resolved by the observations and model. We present theory on error, uncertainty and bias due to unresolved scales for situations where observations contain information on smaller scales than can be represented by the numerical model. The Schmidt-Kalman filter, which accounts for the uncertainties in the unrepresented processes, is investigated and compared with an optimal Kalman filter that treats all scales, and a suboptimal Kalman filter that accounts for the large-scales only. The equation governing true analysis uncertainty is reformulated to include representation uncertainty for each filter. We apply the filters to a random walk model with one variable for large-scale processes and one variable for small-scale processes. Our new results show that the Schmidt-Kalman filter has the largest benefit over a suboptimal filter in regimes of high representation uncertainty and low instrument uncertainty but performs worse than the optimal filter. Furthermore, we review existing theory showing that errors due to unresolved scales often result in representation error bias. We derive a novel bias-correcting form of the Schmidt-Kalman filter and apply it to the random walk model with biased observations. We show that the bias-correcting Schmidt-Kalman filter successfully compensates for representation error biases. Indeed, it is more important to treat an observation bias than an unbiased error due to unresolved scales.